2021
DOI: 10.1109/tmtt.2021.3081710
|View full text |Cite
|
Sign up to set email alerts
|

A 50-nm Gate-Length Metamorphic HEMT Technology Optimized for Cryogenic Ultra-Low-Noise Operation

Abstract: This article reports on the investigation and optimization of cryogenic noise mechanisms in InGaAs metamorphic high-electron-mobility transistors (mHEMTs). HEMT technologies with a gate length of 100, 50, and 35 nm are characterized both under room temperature and cryogenic conditions. Furthermore, two additional technology variations with 50-nm gate length are investigated to decompose different noise mechanisms in HEMTs. Therefore, cryogenic extended K u-band low-noise amplifiers of the investigated technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The cut‐off frequency f T and maximum cut‐off frequency f max are measured as 89, 272, 8 and 18 GHz for InAlAs/InGaAs and InAlAs/InAlAs HEMTs respectively. The results of InAlAs/InGaAs HEMT are in agreement with earlier published results of InGaAs HEMT with L G = 50 nm at 295 K 16 . Furthermore, similar InGaAs based devices with L G = 0.25 μm results f T = 143 GHz and L G = 0.1 μm results f T = 205 GHz also validates the DC and RF performance of the proposed device 17 .…”
Section: C‐v Characteristicssupporting
confidence: 90%
“…The cut‐off frequency f T and maximum cut‐off frequency f max are measured as 89, 272, 8 and 18 GHz for InAlAs/InGaAs and InAlAs/InAlAs HEMTs respectively. The results of InAlAs/InGaAs HEMT are in agreement with earlier published results of InGaAs HEMT with L G = 50 nm at 295 K 16 . Furthermore, similar InGaAs based devices with L G = 0.25 μm results f T = 143 GHz and L G = 0.1 μm results f T = 205 GHz also validates the DC and RF performance of the proposed device 17 .…”
Section: C‐v Characteristicssupporting
confidence: 90%
“…The MMIC is fabricated in a 50-nm gate-length mHEMT technology of Fraunhofer IAF [1], [8] (labeled as "Technology C" in [1]). The 2-D electron gas is confined in an In 0.52 Al 0.48 As/In 0.8 Ga 0.2 As/In 0.52 Al 0.48 As heterostructure.…”
Section: -116-ghz Low-noise Amplifiermentioning
confidence: 99%
“…In the past, this difference initiated, up to some extent, discussions about the ability of mHEMTs to provide ultralow-noise performance under cryogenic conditions at the level of InP HEMTs. However, in recent work [1], we demonstrated that mHEMTs can provide state-of-the-art cryogenic noise performance by the evaluation of different mHEMT technology variations using a Ku-band low-noise amplifier (LNA) monolithic microwave integrated circuit (MMIC). In this work, we present the design, characterization, and results of a 67-116-GHz waveguide LNA module.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, [3] reported that an LNA with x = 80% channel InP HEMT experienced nearly twice the amount of noise compared to x = 65% at 4 K, despite similar noise level for the LNAs at room temperature [3]. A study by Heinz et al [4] indicated that a single In x Ga 1−x As channel with x = 80% in cryogenic metamorphic HEMT LNAs achieved the lowest noise among studied channel structures within the 8-18 GHz frequency range. The same study revealed that a composite In 0.8 Ga 0.2 As/In 0.53 Ga 0.47 As channel displayed a larger noise reduction upon cooling than a In 0.65 Ga 0.35 As/In 0.53 Ga 0.47 As channel, resulting in nearly identical noise temperatures for both structures within the same frequency range at 10 K. To conclude, recent reports of InP HEMTs with various channel indium content suggest a non-trivial dependence with respect to final noise properties of the HEMT and LNA.…”
Section: Introductionmentioning
confidence: 98%
“…Since the power of the qubit is extremely small, the signal-to-noise ratio of the LNA must be highest possible. In the InP HEMT, the In x Ga 1−x As channel plays a decisive role in the final noise properties of the HEMT LNAs [3], [4]. The well-known Fukui equation stipulates that the higher transconductance g m for the HEMT, the lower the noise figure [5].…”
Section: Introductionmentioning
confidence: 99%